La aplicación de estrategias metodológicas en el inter aprendizaje y su incidencia en la motivación de los estudiantes de la Unidad Educativa “Quintiliano Sánchez Rendón, del cantón Buena Fe, Provincia de Los Ríos. - Sinchiguano Toapanta, Miryam (2015)
The present titled investigation work: The application of methodological strategies in the one inter learning and their incidence in the motivation of the students of the Educational Unit "Quintiliano Sánchez Rendón, of the canton Good Faith, County of The Ríos, arose of the necessity of knowing what it is happening to the use of the teaching strategies in the classrooms of classes, since many students demonstrate little attention and interest in learning and it is for this reason that they are not able to reach a good academic yield. The specific objectives that thought about in the investigation are: To investigate on the methodological strategies of inter-learning that are using the educational ones in the students; to know if motivation exists in the students, when carrying out the learning activities in the classroom and to Investigate on the motivation models to motivate the students. And likewise they thought about hypothesis that after the surveys carried out students from the 4to to 7mo year of E.B of the Educational Unit "Quintiliano Sánchez Rendón" of the canton Good Faith, they could be proven and they are the following ones: " The methodological strategies of inter-learning develop dexterities cognitivas in the students. " The first floor level of the students' motivation, causes that it is not always attentive in the learning activities in the classroom. " The application of motivation models, they influence in the yield of the students. It was interviewed to a sample of 175 students and 12 educational of the facility, the same ones that allowed to obtain the conclusions and recommendations on the outlined problem.